Prevalence of latent eosinophilia among occupational gardeners at Babcock University, Nigeria - Ayodele Olushola Ilesanmi; Ginnikachi Jennifer Ekwe; Rosemary Isioma Ilesanmi; Damilola Temitope Ogundele; Jacob Kehinde Akintunde; Oluwasogo Adewole Olalubi (Asian Pacific Journal of Tropical Biomedicine, 2016)
Objective: To determine the level of eosinophils present in the blood and sputum samples, presumably as a result of continual occupational exposure to allergens while on duty, as gardeners at Babcock University, Nigeria. Methods: Haemocytometer and Olympus microscope were utilized to estimate eosinophils population in 44 blood samples and 21 sputum samples respectively. Results: Relationship between the occurrence of eosinophil in blood and the exposure period among Babcock University gardeners had a positive correlation (r = + 0.08, t = 4.55, P < 0.05). It was found that blood eosinophil count in these workers correlated with the length of exposure period. Conclusions: The nature and the gardening activities are not a risk factor that significantly affect eosinophil level but duration of exposure to allergens. However, all safety precautionary kits and wears should be enforced and embraced by the concerned occupational gardeners so as to avert and subvert its pre-disposing deleterious effect on them.